La région Bourgogne : un hôtel de région construit en secteur sauvegardé dans le goût des années 1970 - Julien Defillon (In Situ)
This paper deals with history, architecture and decoration of the Burgundy ‘hotel de region’, its administrative and government centre, built between 1978 and 1980. The architects Roger-Martin Barade and François Ruault succeeded in creating a building which is representative of the evolution of the place of contemporary architecture in ancient and heritage sites in France during the 1970s, and of tastes where decoration, furniture and interior fittings are concerned in the realm of the French administration during the same decade. This study also focuses on the employment of some celebrated artists (Pierre Sabatier, Denis Morog and Michel Boyer) whose works were characterised by reflection on how to integrate art into architecture. The architecture of the building as a whole reflects the different evolutions of the project in order to take into account heritage conservation requirements.